STUDENT COMMUNICATION ETHICS WITH THE TEACHERS OF DAYAH JAMIAH AL-AZIZIYAH SAMALANGA (Perspective of Islamic Communication Ethics) - Zulfikar Arahman; Muhibuddin Muhibuddin; Muhammad Aminullah (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
This study examines the Ethics of Communication between students and the teacher at Dayah Jamiah Al-Aziziyah Samalanga, where as in this study will discuss the forms and ethics of communication that exist between students and the teacher. Communication between the students and the teacher of Dayah Jamiah Al-Aziziyah is definitely established on various occasions, so that there is no activity without communication. But the communication that is established is still limited to the form of communication that has not led to ethics in communication, even though communication ethics is something very important in the communication process. So, the focus of this research is on how the ethics of communication between students and the teacher at Dayah Jamiah Al-Aziziyah Samalanga. This study uses qualitative research with the type of field research, namely a field study that examines the ethical issues of communication between students and the teacher in the perspective of Islamic communication. The data collection technique was carried out by observing, interviewing and documenting the ethics of communication between students and the teacher in various aspect. This study aims to determine the ethics of communication between students and the teacher at Dayah Jamiah Al-Aziziyah Samalanga, where the communication ethics used are very good and perfect. With good communication ethics between students and the teacher, it is easier to establish communication because they take care of each other in communicating. Communication ethics is one aspect that needs to be considered in communicating with anyone, including communication between students and the teacher at Dayah Jamiah Al-Aziziah.